The Effect of E-Service Quality and E-Trust on E-Loyalty with E-Satisfaction as an Intervening for Mobile Banking User - Elsha Melinda; Osly Usman; Shandy Aditya (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2023)
The purpose of this study is to determine the effect of e-Service Quality and e-Trust on e-Loyalty with e-Satisfaction as an Intervening on m-BCA customers. This study uses a quantitative method with a survey instrument. Data was collected using a non-probabilty sampling technique, namely purposive sampling by taking a sample of 150 respondents who had used m-BCA at least three times in the last six months. Then the respondents' answers that have been obtained are processed using the Partial Least Square-Path Modeling method using SmartPLS 3.0 software. From hypothesis testing in this study, the results showed that 1) e-Service Quality has a positive and significant effect on e-Satisfaction, 2) e-Trust has a positive and significant effect on e-Satisfaction, 3) e-Satisfaction has a positive and significant effect on e-Loyalty, 4) e-Service Quality has a positive and significant effect on e-Loyalty, 5) e-Trust has a positive and significant effect on e-Loyalty, 6) e-Service Quality has a positive and significant effect on e-Loyalty through e-Satisfaction and 7) e-Trust has a positive and significant effect on e-Loyalty through e-Satisfaction. This means that e-Service Quality and e-Trust can be improved so that it will have an impact on e-Satisfaction so that it can also have an impact on the e-Loyalty of customers who use m-BCA. keywords: e-loyalty, e-satisfaction, e-service quality, e-trust, m-bca